Examine the Outcomes of Surgical Procedures in Patients with Giant Cell Tumors (Medical Forum Monthly, 2020)
Objective: To examine the outcomes of different surgical procedures in patients with giant cell tumor also determine the frequency of involved bone required surgical treatment.Study Design: Retrospective study.Place and Duration of Study: This study was conducted at the Department of Orthopedic & Traumatology, Qazi Hussain Ahmad Medical Complex Nowshera from January 2018 to March 2020.Materials and Methods: Sixteen patients of both genders presented with biopsy proven giant cell tumor were analyzed in this study. Patients detailed demographic including age, sex and residence were recorded after written consent. Types of bones and different surgical procedures for the treatment were examined. Outcomes of surgical treatment were examined by Musculo Skeletal Tumor Society score (MSTS). Follow-up was taken at 1 year after surgery.Results: Ten (62.5%) patients were males and 6 (37.5%) were females. 3 (18.75%) patients were ages less than 20 years, 11 (68.75%) patients were ages 20 to 40 years and 2 (12.5%) patients had ages above 40 years. Pain and swelling was commonly found symptom in 8 (50%) patients. Distal femur was the commonest site in 5(31.25%) patients followed by proximal tibia in 4 (25%) patients. Curettage and bone cementation was the commonly performed surgical procedure in 5 (31.25%), followed by wide excision of bone and cementation and implant in 4 (25%) patients, 3 (18.75%) patients received curettage and bone grafting, 2 (12.5%) had received disarticulation, 1 (6.25%) patient were received arthroplasty and amputation was done in 1 (6.25%) patient. Recurrence was found in 1 patient with curettage and bone grafting and 2 with curettage and bone cementation. The mean MSTS score was 26.2 out of 30.Conclusion: Giant cell tumor is commonly found in patients with 3rd and 4th decade of life. Distal femur and proximal tibia were the most common site of bones involved and curettage and cementation was the commonly performed surgical procedure. Patients with giant cell tumor were on high risk of recurrence after surgical treatment.